Bastards everywhere: The beech, a Eurasian species mosaic - Schulze, Ernst-Detlef; Grimm, Guido W. (Biologie in unserer Zeit, 2022)
Beech (genus Fagus) is one of the best-known deciduous trees in the northern hemisphere. On the basis of numerous fossils, its history can be traced back to the Late Cretaceous period (c. 80 million years ago). Possibly because of its complex genetics and only a few accepted species, it has remained largely unnoticed by systematists and phylogeneticists. At the same time however, it is the key model for reticulate evolution, a common phenomenon in plant speciation. Species emerge and disappear (become extinct) due to the interaction of gene flow and gene drift. In the course of this process, genetic material is exchanged between species. Current species are the product of a dynamic past which was influenced by global processes such as tectonics and climate change. As a result, the nuclear and plastid genomes of current beech species carry diverse traces of earlier interspecific contacts (hybridization). They are genetic mosaics reflecting the dynamic history of their genus. This article summarizes the newest insights into the complex, highly reticulate evolution of beech species in Europe and Asia.